2017
DOI: 10.1108/mhrj-09-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable young people’s experiences of child and adolescent mental health services

Abstract: Purpose The purpose of this paper is to explore the experiences of vulnerable young people in using a local child and adolescent mental health service (CAMHS). Design/methodology/approach A mixed methods design was employed in which participants completed the self-report Experience of Service Questionnaire (CHI ESQ) (n=34), and a subgroup completed individual semi-structured interviews (n=17). CHI ESQ satisfaction data were also compared with a national data sample provided by the Child Outcomes Research Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Young people can need different types of professional boundaries depending on their risk or resilience profiles (Ungar et al, 2018). Importantly, young people want the time and opportunity to build positive rapports and establish stable relationships as these are crucial to ongoing engagement and maintaining participation in mental health care (Davison et al, 2017; Jones et al, 2017; Persson et al, 2017). This supportive rapport, built on trust and confidentiality, provides a young person with the necessary context to engage in collaborative care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Young people can need different types of professional boundaries depending on their risk or resilience profiles (Ungar et al, 2018). Importantly, young people want the time and opportunity to build positive rapports and establish stable relationships as these are crucial to ongoing engagement and maintaining participation in mental health care (Davison et al, 2017; Jones et al, 2017; Persson et al, 2017). This supportive rapport, built on trust and confidentiality, provides a young person with the necessary context to engage in collaborative care.…”
Section: Resultsmentioning
confidence: 99%
“…The third theme identified in this review concerns findings regarding the ability of the helper to discuss, inform, and offer an individualized and collaborative treatment plan to young people. Young people want to be involved in decisions about their care and have a choice of which intervention they would like to try; if they are excluded from this decision-making process, then there is a greater chance they will disengage from treatment (Davison et al, 2017; Draucker, 2005; Gilchrist & Sullivan, 2006; Neilson et al, 2014; Persson et al, 2017; Quinn et al, 2009; Simmons et al, 2011; Wilson & Deane, 2001). In particular, young people reported wanting a helper that was knowledgeable about mental health, providing them with information and high-quality guidance (Draucker, 2005; Gilchrist & Sullivan, 2006; Neilson et al, 2014; Quinn et al, 2009; Simmons et al, 2011; Williams, 2012; Wilson & Deane, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two participants felt they could not seek help for fear of what others may think (Flack, 2018), with adolescents in another study reporting reluctance to access a post-traumatic stress intervention due to peers not wanting attention brought to the friend group (van der Water et al, 2018). Others reported that seeking counselling was 'weird' or 'crazy' and would encourage social exclusion or judgement (Davison, Zamperoni, & Stain, 2017;Lindsey et al, 2013), contrasting with others' views of help-seeking as encouraging independence in youth (Lindsey et al, 2013). A lack of understanding of OCD-related difficulties was found to delay help seeking in adolescents from 3 months to 8 years (Keyes et al, 2017).…”
Section: Lack Of Help-seekingmentioning
confidence: 99%